Human Impact on the Environment and the Increased Likelihood of Pandemics - Soage, Ana-Belén (Routledge, 2024)
COVID-19 is the fourth pandemic to hit the world since the turn of the millennium, after SARS, swine flu, and MERS. It has been the most devastating so far, thus focusing global attention, but scientists have warned about the threat posed by pandemics for the last three decades. A major driver for that threat is the human impact on nature during the new geological era known as the Anthropocene. This chapter looks at some of pandemics' main factors: disruption of the environment, which leads to human contact with zoonosis carriers; urbanisation and globalisation, which facilitate the proliferation and spread of pathogens; intensive animal farming, which renders diseases more lethal and prone to crossing species barriers; and finally, climate change, which expands the geographical range of species that can transmit zoonoses. This chapter concludes by providing an overview of initiatives that broaden our notion of security to include the ecological and socio-economic dimensions and argues for rethinking our development model.
Es un capítulo del libro: Akıllı, E., Güneş, B., & Gökbel, A. (Eds.). (2023). Diplomacy, Society and the COVID-19 Challenge (1st ed.). Routledge.
Keywords: environment; pandemics; zoonosis; Scopus